Daniel Coit Gilman and the Birth of the American Research University - Benson, Michael T. (Book collections on Project MUSE., 2022)
Ultimately, the book shows, Gilman and his colleagues forced all institutions to reexamine their own model and to make the requisite changes to adapt, survive, thrive, compete, and contribute.